2020
DOI: 10.1093/neuonc/noaa092
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of hippocampal-sparing whole brain irradiation with simultaneous integrated boost for metastatic cancer

Abstract: Background Advanced radiotherapeutic treatment techniques limit the cognitive morbidity associated with whole-brain radiotherapy (WBRT) for brain metastasis through avoidance of hippocampal structures. However, achieving durable intracranial control remains challenging. Methods We conducted a single-institution single-arm phase II trial of hippocampal-sparing whole brain irradiation with simultaneous integrated boost (HSIB-WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Other impaired cognitive constructs in the WBRT studies were EF (29–38%), fine motor coordination (31%), information processing speed (28%), and verbal fluency (7–32%). Even though Westover et al [41] observed a decline in 17% of their patients ( N = 18) regarding L&M performance, on the group level, no significant changes from baseline were found for the other cognitive constructs [41]. Nevertheless, large variations in mean relative change were found for all cognitive constructs (L&M, information processing speed, EF, and verbal fluency).…”
Section: Resultsmentioning
confidence: 97%
“…Other impaired cognitive constructs in the WBRT studies were EF (29–38%), fine motor coordination (31%), information processing speed (28%), and verbal fluency (7–32%). Even though Westover et al [41] observed a decline in 17% of their patients ( N = 18) regarding L&M performance, on the group level, no significant changes from baseline were found for the other cognitive constructs [41]. Nevertheless, large variations in mean relative change were found for all cognitive constructs (L&M, information processing speed, EF, and verbal fluency).…”
Section: Resultsmentioning
confidence: 97%
“…This also includes patients who have been treated with WBRT for multiple BMs. As a result, BM patients are now more frequently affected by a treatmentassociated long-term neurocognitive decline; therefore, current approaches are trying to preserve cognitive function following WBRT [10,11,[14][15][16][17][18][19][20]. The ongoing multicentric HIPPORAD (NOA-14) trial addresses this approach (results are pending) [16].…”
Section: Volume Of Metastasismentioning
confidence: 99%
“…Moreover, Gondi et al have suggested a remarkable benefit in speaking, memory, and patient-reported symptoms, including fatigue and interference in daily living, following WBRT associated with memantine [ 31 ]. Westover et al have investigated, in a single-arm phase II trial, the hippocampal-sparing WBRT with a simultaneous integrated boost (HSIB-WBRT) delivered to BM in 50 patients reporting a median decline in Hopkins Verbal Learning Test-Revised delayed recall (HVLT-R DR) at three months of 10.6%, a cumulative incidence of intracranial recurrence of 8.8%, and a median OS of nine months [ 32 ].…”
Section: Local Treatments For Bm and Lm From Breast Cancermentioning
confidence: 99%